PROBLEMS AND SOLUTIONS IN WORKING PROBABILITY AND COMBINATORICS PROBLEMS - * (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotatsiya; An issue that appears difficult in one discipline may become simple to tackle when seen from a different perspective. In this note, a combinatorial problem is presented as a probability problem, making it easier to solve.